GENDER ROLE CONSTRUCTION AND ITS IMPACT PORTRAYED IN THE GLASS MENAGERIE PLAY (KONTRUKSI PERAN GENDER SERTA DAMPAKNYA DALAM DRAMA THE GLASS MENAGERIE) (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2015)
The aims of this study are to explain how gender role concept constructed toward the children and also to identify the consequences of gender role differences that profoundly affect the quality of individual lives as reflected in play. I employed Tennessee William’s The Glass Menagerie play as the object of my study. This study was a qualitative study with Sociological approach. The data were in a form of words, phrases, sentences, and dialogues. They were collected by reading the script of the drama thoroughly, interpreting, triangulating, identifying, inventorying, and reporting the data. Some relevant theories were also used to support the analysis and answer the statements of problem. From this study, it can be concluded that parent exerts strong influences on person in perceiving their gender role concept. Masculine and feminine are quite conventional and the expectation connected to each gender become important to fulfill. However, the presence of gender roles gives consequences in life. It creates different gap toward men and women existence because women tend to be more dependent on men because they are powerless and subordinate to men. In fact, unequal power and position heighten gender based social inequalities.